A large memory, high transfer rate VME data acquisition system for the JET correlation reflectometer - Cruz, Nuno (2002)
The current paper presents a large memory giving special emphasis to the architecture and suitability of the Linux OS for this type of applications. The system will be used on the joint european torus new correlation reflectometers composed by four microwave channels with four analogue signals each. All sixteen signals will be acquired by 12-bit VME fast acquisition channels at 2 Msamples/s achieving a total data rate of 60MB/s. Slower VME acquisition channels, with 16-bit resolution and sampling rates up to 250 ksamples/s, can also acquire these 16 signals. Two dedicated digital signal processors run an algorithm over this acquired data to avoid the use of the old KG8B root mean square analogue circuits as well as to control and to generate all the timing and acquisition clocks needed by the system.